EDUCATIONAL EFFECTIVENESS IN INCREASING COASTAL POLLUTION AWARENESS USING FUZZY BASED ALGORITHMS - (:unkn) unknown (PARLAR SCIENTIFIC PUBLICATIONS (P S P), 2014)
During the summer, the shores in Istanbul are used for various recreational purposes. Frequent and careless use of sea water can not only endanger one's personal health but also disrupt the existing water quality. Various reasons for this situation may range from having insufficient knowledge pertaining to environmental protection, not having sufficient access to environmental protection outlets, and not being exposed to recent and updated educational materials concerning environmental protection and conservation. The present study attempts to determine the level of awareness onenvironmental protection (especially along the shores of Istanbul) using fuzzy logic based algorithms A survey, developed specifically for this study, was administered to 9 different academic institutions, with four different age groups during the academic years of 2005-2006 and 2011-2012. These groups were randomly selected according to their age and level of education. Research indicates that a knowledge and information gap concerning shore and environmental awareness exists. In this study, a pre-test and post-test design was applied with various age and education level groups. After conducting the training procedures, the results were evaluated via using fuzzy based algorithms. It was found that by providing the proper education, heightened awareness can be attained. Findings suggest that if both current and future generations are trained with the proper, accurate and updated information on sea water preservation, environmental protection, and health awareness, they will be able to utilize, act on, and preserve their surroundings in the future.
Keywords: Health awareness; Environmental protection; Istanbul; Environmental Education; Fuzzy Logic; CONSERVATION